A Review of the Circular Economy and its Implementation - Almas Heshmati (Institute for the Study of Labor (IZA), 2015)
Circular economy (CE) is a sustainable development strategy that is being proposed to tackle urgent problems of environmental degradation and resource scarcity. CE's 3R principles are to reduce, reuse and recycle materials. The principles account for a circular system where all materials are recycled, all energy is derived from renewables; activities support and rebuild the ecosystem and support human health and a healthy society and resources are used to generate value. This study is a review of the rapidly growing literature on CE covering its concept and current practices and assessing its implementation. The review also serves as an assessment of the design, implementation and effectiveness of CE related policies. It first presents the concept of CE and compares it with the current linear economy of taking materials, producing goods and disposing waste. It explains why it is imperative to move away from a linear economy towards regenerative sustainable industrial development with a closed loop. The paper then introduces current practices that have been introduced and discusses standards for the assessment of CE's development and performance. The main focus here is on providing a summary of the data analysis of key CE indicators to give a picture of CE practices. Third, based on an analysis of literature, the paper identifies the underlying problems and challenges to CE in an entrepreneurial perspective. Finally, the review provides a conclusion on CE's current development and gives policy suggestions for its future development as part of an entrepreneurial and innovative national level development strategy.
Keywords: E01; F18; F64; H23; O44; Q50; Q53; Q55; Q58; R11; 330; circular economy; environmental policy; national development strategy; sustainable development strategy; entrepreneurial strategy